PREDIKSI PENERIMAAN KARYAWAN BAGIAN DESAIN PADA EVENT ORGANIZER PT. SEIRAH WISATA MENGGUNAKAN ALGORITMA C4.5 - Hendriyanto , Bei harira (STMIK DHARMA WACANA, 2021)
ABSTRACT Human resources design section at an Event Organizer is a vital part considering that the design will be seen by the event participants in addition to the technical events. The selection of employees who understand design and have extensive experience is important. The process of selecting employees in the design field can sometimes be difficult to predict if there are several prospective employees with balanced abilities. From the calculation results of the dataset as many as 14 applicants using the C4.5 algorithm, the highest Gain Ratio value obtained in the design Ability and Experience = 0.7172, Origin of Schools = 0.0511 and Age = 0.0205. Keywords : event organizer, C4.5 algorithm, prospective employees, Gain Ratio